1970
DOI: 10.2527/jas1970.303388x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding-Fasting Interval on Finishing Pigs: Blood Urea and Serum Lipid, Cholesterol and Protein Concentrations

Abstract: A system of restricted feeding in which feed is entirely withheld for intervals of 24, 48 or 72 hr. following a 24-hr. period of ad libitum feeding in continuous sequence throughout the finishing period depresses weight gain and efficiency of feed utilization in direct relation to duration of the fasting period and has marked associated effects on carcass measurements, gland and organ weights and a small effect on fatty acid composition of the back fat (Veum et al., 1970). Cohn (1963) and Leveille and Hanson (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Following an opposite direction in the factor, with a positive loading (0.6), was plasma urea concentration. Basal plasma urea is well controlled, but it is affected by prolonged fasting ( Veum et al, 1970 ) and, in this study, was not associated with crude protein intake (data not shown). A first assumption would be that pigs that go for long periods without feed present a plasma urea drop, and they will eat faster when they present themselves to the feeder once they are hungry.…”
Section: Resultsmentioning
confidence: 47%
“…Following an opposite direction in the factor, with a positive loading (0.6), was plasma urea concentration. Basal plasma urea is well controlled, but it is affected by prolonged fasting ( Veum et al, 1970 ) and, in this study, was not associated with crude protein intake (data not shown). A first assumption would be that pigs that go for long periods without feed present a plasma urea drop, and they will eat faster when they present themselves to the feeder once they are hungry.…”
Section: Resultsmentioning
confidence: 47%
“…Feed was removed from the Fasted pigs (PP, n = 8; M, n = 8) for a period of 72 h prior to euthanasia. The duration of fasting for 72 h was based on the foundational studies reported by Veum et al. (1970) and Steffen et al.…”
Section: Methodsmentioning
confidence: 99%
“…Feed was removed from the Fasted pigs (PP, n = 8; M, n = 8) for a period of 72 h prior to euthanasia. The duration of fasting for 72 h was based on the foundational studies reported by Veum et al (1970) and Steffen et al (1981), who reported that fasted growing-finishing pigs did not clinically exhibit fasting-induced metabolic symptoms until they had been fasted for at least 72 h. After 72 h, dramatic measurable differences in weight gain and circulatory parameters, such as triglycerols and cholesterol, will occur. Therefore, acute fasting is defined as a 72 h period of time during which the animal is deprived of food and a chronic fast would define a period of time during which food was deprived longer 72 h.…”
Section: Experimental Designmentioning
confidence: 99%
“…Finishing pigs (49 to 90 kg) adapted to an every-third-day feeding program (Veum et al, 1970) exhibit an increase in blood urea N 10 h after the meal followed by gradual reductions at both 34 and 54 h postprandial. Our N excretion data follow the pattern of this blood urea N data.…”
Section: Discussionmentioning
confidence: 99%